When and Why Leaders’ Helping Behavior Promotes Employees’ Thriving: Exploring the Role of Voice Behavior and Perceived Leader’s Role Overload - Chen, Long; Zhang, Zhen-Duo; Jia, Wen-Tong (Frontiers in Psychology, 2020)
Employees who thrive contribute to their organization’s competitive advantage and sustainable performance. The aim of this study was to explore how employees’ thriving is shaped by their leaders’ behavior. Drawing on social learning theory, we examined the relationship between perceived leader’s helping behavior and employee’s thriving. Positing voice behavior as mediator and perceived leader’s role overload as moderator, we constructed a moderated mediation model. Using 205 daily data from 51 employees in various industries, we found that perceived leader’s helping behavior had a positive effect on employee’s thriving at work and that employee’s voice behavior mediated this effect. With the increase of perceived leader’s role overload, the positive relationship between perceived leader’s helping behavior and employee’s voice behavior as well as the indirect effect of perceived leader’s helping behavior on employee’s thriving via employee’s voice behavior were increasingly strong. The findings of our study have implications for research on employees’ thriving at work, leaders’ helping behavior, and social learning theory. There are also practical implications for the behavior of leaders who experience role overload.